Insulin-Like Growth Factor-1 and Selected Insulin-Like Growth Factor Binding Protein Concentrations during an Ultramarathon Sled Dog Race - Matthew W. Brunke; Christopher W. Frye; Corri B. Levine; Cristina Hansen; Joseph J. Wakshlag (The Scientific World Journal)
The objective of this study was to investigate the effects of running a 1000-mile (1600 km) endurance sled dog race on serum insulin-like growth factor-1 (IGF-1) and insulin-like growth factor binding proteins 1 and 3 (IGFBP-1 and IGFBP-3). Serum was examined from 12 sled dogs prior to the race, at midrace (approximately 690 km), and again at the finish. IGF-1, IGFBP-1, and IGFBP-3 were assessed using radioimmunoassay or enzyme linked immune-absorbance assays. Mean prerace concentrations were significantly higher than midrace and end-race concentrations at 215.93 ± 80.51 ng/mL, 54.29 ± 25.45 ng/mL, and 55.53 ± 28.25 ng/mL, respectively (P<0.001). Mean IGFBP-1 concentrations were not different across these time periods at 24.1 ± 15.8 ng/mL, 25.7 ± 14.0 ng/mL, and 26.6 ± 17.6 ng/mL, respectively. IGFBP-3 concentrations showed a modest significant decrease across time periods at 3,067 ± 2,792 ng/mL, 2,626 ± 2,310 ng/mL, and 2,331 ± 2,301 ng/mL, respectively (P<0.01). Endurance sled dogs show a precipitous drop in serum IGF-1 concentrations. These differences may be related to fuel utilization and excessive negative energy balance associated with the loss of body condition during racing. The relative stability of IGFBP-1 and IGFBP-3 suggests that IGF-1 anabolic signaling is diminished during ultramarathon racing. Further studies comparing the influence of time and duration of exercise versus negative energy balance on serum IGF-1 status are warranted to better understand exercise versus negative energy balance differences.